Analisis Penerapan Insentif PPh Final UMKM Ditanggung Pemerintah - Miftah Fauzi; Yeti Apriliawati (Indonesian Accounting Literacy Journal, 2021)
This research has a purpose to find out how the application of final income tax incentive borne by the Government MSMEs in KPP Pratama Kuningan, as well as the obstacles encountered and the solutions taken. The method used in this research is qualitative research methods. Data collection techniques are carried out through interviews, and documentations. Data analysis techniques are carried out through data collection, data reduction, data display, conclution drawing and verification. The validity of the data was tested by source triangulation. The results showed that the application of final income tax incentives for MSMEs at KPP Pratama Kuningan was good. However, there are obstacles in the socialization process, differences in taxpayer data, and an error in the DJP Online system. The resolution of the obstacles that were carried out included using social media in disseminating information, make an official report (BA) Changes, providing feedback to the DJP Online system holder, and providing consultation facilities via WhatsApp Help Desk. This solution has increased taxpayers who receive final income tax incentives borne by the government.